Maternal Burnout Syndrome: Contextual and Psychological Associated Factors - Lebert-Charron, Astrid; Dorard, Géraldine; Boujut, Emilie; Wendland, Jaqueline (Frontiers in Psychology, 2018)
Background: Becoming a parent is one of the most significant experiences in a woman’s life. Including substantial and long-lasting mental, social and physical charge, the parenting experience may also be a potentially stressful and overwhelming task. Since the eighties, the notion of parental burnout syndrome has gained increasing attention, but its contextual and psychological factors need to be better identified. Aims: To investigate a large array of contextual and psychological factors associated with maternal burnout syndrome in a French community-based population in order to contribute to better operationalize the notion of parental burnout and to explore its determinants. Method: A total of 304 French-speaking mothers (mean age=34.8 years, SD=6.72) completed a set of questionnaires including a sociodemographic form (in order to gather general information about the mothers, their spouses and children living at home). The Perceived Stress Scale, the Maslach Burnout Inventory adapted to parents (MBI-parental), the Hospital Anxiety and Depression Scale, the Parental Stress Index-Short Form and the Ways of Coping Checklist were used in this study. Results: Multivariate linear regression analyses revealed that scores on the MBI-parental version were strongly and positively associated with depressive and anxiety symptoms, as well as with perceived stress related to parenthood and parenting stress levels. Moreover, using the task-oriented coping style in parenthood was strongly and positively associated with personal accomplishment. Conversely, some sociodemographic characteristics were found to be negatively associated with maternal burnout: being employed, working full time and being a mother living without a coparent. Conclusion: The construct of maternal burnout syndrome seems to be linked to a conjunction of psychological and contextual factors associated with maternal exhaustion. The implication of the results for prevention and intervention strategies are discussed.